Enhancing emotion recognition in virtual reality: a multimodal dataset and a temporal emotion detector - Qu, Chenxin; Che, Xiaoping; Yang, Yafei; Zhang, Zhongwei; Chang, Enyao; Zhang, Jianing; Zhu, Hongwei; Yang, Ling (Frontiers in Psychology, 2025)
Emotion is a complex psychophysiological phenomenon elicited by external stimuli, exerting a profound influence on cognitive processes, decision-making, and social behavior. Emotion recognition holds broad application potential in healthcare, education, and entertainment. With virtual reality (VR) emerging as a powerful tool, it offers an immersive and controllable experimental environment. Prior studies have confirmed the feasibility and advantages of VR for emotion elicitation and recognition, and multimodal fusion has become a key strategy for enhancing recognition accuracy. However, publicly available VR multimodal emotion datasets remain limited in both scale and diversity due to the scarcity of VR content and the complexity of data collection. The shortage hampers further progress. Moreover, existing multimodal approaches still face challenges such as noise interference, large inter-individual variability, and insufficient model generalization. Achieving robust and accurate physiological signal processing and emotion modeling in VR environments thus remains an open challenge. To address the issues, we constructed a VR experimental environment and selected 10 emotion-eliciting video clips guided by the PAD(Pleasure-Arousal-Dominance) model. Thirty-eight participants (N=38) were recruited, from whom electrodermal activity, eye-tracking, and questionnaire data were collected, yielding 366 valid trials. The newly collected dataset substantially extends the publicly available VREED dataset, enriching VR-based multimodal emotion resources. Furthermore, we propose the MMTED model (Multi-Modal Temporal Emotion Detector), which incorporates baseline calibration and multimodal fusion of electrodermal and eye-tracking signals for emotion recognition. Experimental results demonstrate the strong performance of the MMTED model, achieving accuracies of 85.52% on the public VREED dataset, 89.27% on our self-collected dataset, and 85.29% on their combination.